Concurrent pyoderma gangrenosum and subcorneal pustular dermatosis in a patient with monoclonal IgA/λ gammopathy - Ya-Wen Hsiao; Hua-En Lee; Tseng-Tong Kuo (Wolters Kluwer Medknow Publications, 2011)
Subcorneal pustular dermatosis (SPD) and pyoderma gangrenosum (PG) are two neutrophilic dermatoses. Coexistence of these diseases in the same patient is rare and may be a strong indicator of IgA dysglobulinemia. We describe a 69-year-old man who presented with waxing and waning flaccid pustules covering his trunk and four limbs. Poorly healing ulcerations, which usually progressed into larger nodules after debridement, were also noted. Repeated cultures were negative for bacteria, and the patient was diagnosed with SPD and PG. Serum protein electrophoresis and immunofixation revealed a monoclonal IgA lambda protein. A subsequent bone marrow biopsy revealed a normocellular marrow. While PG and SPD can occur individually in a variety of associated diseases, such as rheumatoid arthritis, systemic lupus erythematosus and inflammatory bowel disease or infection; however, their coexistence is strongly indicative of IgA dysglobulinemia.